Mitteilungen. - Technische Hochschule Berlin.; Berlin. (Springer., 1883)
Vols. for 1883-1908 include reports of research of the Chemisch-technische Versuchs-Anstalt of Berlin, the Mechanisch-Technische Versuchs-Anstalt of the Technische Hochschule of Berlin, and of other similar institutions.
Supplements accompany some vols.
Frequency varies.
Vols. for 1883-1908 include reports of research of the Chemisch-technische Versuchs-Anstalt of Berlin, the Mechanisch-Technische Versuchs-Anstalt of the Technische Hochschule of Berlin, and of other similar institutions.
Absorbed the Mitteilungen of the Max-Planck-Institut für Metallforschung (formerly the Kaiser Wilhelm-Institut für Metallforschung) in 1923
Keywords: Testing; Engineering / Periodicals